Efetividade de um treino funcional na prevenção de quedas em idosos institucionalizados - Silva, Lilian Atalaia da [UNIFESP] (2018)
Objective: To evaluate the effects of a functional exercise program on kinematic gait patterns and the prevention of falls risk in institutionalized elderly people for 12 months. Two long-term public institutions participated, one belonging to the Control Group (CG) and the other to the Experimental Group (EG). Methods: Each group consisted of 20 elderly women who were evaluated before and after the intervention. The global cognitive status was measured by the Mini Mental State Exam; the executive functions through the Trail Making Test Parts A and B, and the visuospatial ability by the Visuospatial test. To evaluate the functionality, we used the Berg Functional Balance Scale, Timed up and go (TUG) and "30s Chair Stand". Additionally, we used the Geriatric Depression Scale (GDS), the Falls International Efficacy Scale (FES-I) and history of falls in the last 12 months. The EG was submitted to an intervention protocol through a functional training program, focusing on the improvement of the static, dynamic balance and gait training in order to prevent future falls. The program consisted of two weekly sessions lasting 60 minutes each for three months. Results: There were no statistically significant differences in the anthropometric data, global cognition and functionality in the pretest. Regarding the frequency of falls, 10 elderly women in the EG reported falling, while eight in the CG did so. After the protocol, EG improved significantly in the Free walking (t = 4.1, p = 0.001) and walking + cognitive + obstacle tasks (t = 3.3, p =0.004). There was a statistically significant difference in the Trail B, time (t = 2.44, p = 0.02) and number of errors (t = 6.04, p = 0.00), number of errors Trail A (Wilcoxon = -2.46; = 0.01) and the Visuospatial test (t = -4.27, p = 0.00). The same happened for all functional variables, that is, 30s Chair Stand Test (t = -2.02, p = 0.05); Berg (t = - 3.10, p = 0.006) and FES-I (t = 5.49, p = 0.00), while the CG had a lower performance after three months in all respects. During 12 months of follow-up, seven elderly women from the CG fell, 85% of these were recurrent, whereas the experimental group had two reports of falls. There was a statistically significant correlation between the number of falls and the group the elderly belonged to (r =0,36, p = 0.022). Conclusion: The functional training protocol was able to improve several cognitive and functional aspects, as well as to prevent risk of falls for 12 months.